Convexity, magnification, and translation: The effect of managerial option-based compensation on corporate cash holdings - Belghitar, Yacine; Clark, Ephraim (Blackwell Publishing Ltd, 2014)
Using the distinctions among the convexity, magnification, and translation effects, we identify the pertinent parameters and examine empirically the relation between cash holdings and option-based managerial compensation. We show that changes in delta reduce the effects of magnification and convexity on managerial risk aversion. We also provide evidence that there is a negative relation between the option-based incentives delta and vega and cash holdings. These results are robust when incentives are extended to include all executive board members and when the sample is broken down according to different risk characteristics.